Fibroblasts in rheumatoid arthritis: novel roles in joint inflammation and beyond - Elpida Neofotistou-Themeli; Elpida Neofotistou-Themeli; Panagiota Goutakoli; Panagiota Goutakoli; Theodoros Chanis; Theodoros Chanis; Maria Semitekolou; Maria Semitekolou; Eirini Sevdali; Eirini Sevdali; Prodromos Sidiropoulos; Prodromos Sidiropoulos (Frontiers in Medicine)
High-throughput technologies in human and animal studies have revealed novel molecular and cellular pathways involved in tissue inflammation of rheumatoid arthritis (RA). Fibroblasts have been in the forefront of research for several decades. Subpopulations with specific phenotypic and functional properties have been characterized both in mouse models and human disease. Data supporting the active involvement of fibroblasts in immune responses and tissue remodeling processes, as well as their central role in promoting clinical relapses and contributing to treatment resistance, have clearly reshaped their role in disease evolution. The lung is an important non-synovial component of RA both from a clinical and an immunopathogenic aspect. Interstitial lung disease (ILD) is a significant contributor to disease burden affecting morbidity and mortality. Although our knowledge of ILD has progressed, significant gaps in both basic and clinical science remain, posing hurdles to efficient diagnosis, prediction of disease course and its effective treatment. The specific role and contribution of fibroblasts to this process has not been clearly defined. The focus of this review is on fibroblasts and their contribution to RA and RA-ILD, presenting data on genetics and immune responses associated with RA-ILD in humans and animal models.